2018
DOI: 10.14336/ad.2017.0416
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil Factor 3, Cholinesterase and Homocysteine: Potential Predictors for Parkinson’s Disease Dementia and Vascular Parkinsonism Dementia in Advanced Stage

Abstract: Trefoil factor 3 (TFF3), cholinesterase activity (ChE activity) and homocysteine (Hcy) play critical roles in modulating recognition, learning and memory in neurodegenerative diseases, such as Parkinson’s disease dementia (PDD) and vascular parkinsonism with dementia (VPD). However, whether they can be used as reliable predictors to evaluate the severity and progression of PDD and VPD remains largely unknown. Methods: We performed a cross-sectional study that included 92 patients with PDD, 82 patients with VPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 78 publications
1
33
1
Order By: Relevance
“…Parkinson's disease patients frequently suffer from mild cognitive impairment (MCI) (MoCA score more than 21 and less than 26) (Litvan et al, 2012), who are at higher risk of developing dementia compared to PD patients with normal cognition (PD-NC) (Kehagia et al, 2010). Several lines of evidence suggested the inflammatory risk factors (Trefoil Factor 3,neutrophils,lymphocytes,et al) in PD may modulate underlying neurodegeneration particularly in relation to dementia (Stojkovic et al, 2018;Zou et al, 2018;Nicoletti et al, 2020;Wang et al, 2020). It is promising to detect MRI-visible EPVS burden as a marker of cognitive decline in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease patients frequently suffer from mild cognitive impairment (MCI) (MoCA score more than 21 and less than 26) (Litvan et al, 2012), who are at higher risk of developing dementia compared to PD patients with normal cognition (PD-NC) (Kehagia et al, 2010). Several lines of evidence suggested the inflammatory risk factors (Trefoil Factor 3,neutrophils,lymphocytes,et al) in PD may modulate underlying neurodegeneration particularly in relation to dementia (Stojkovic et al, 2018;Zou et al, 2018;Nicoletti et al, 2020;Wang et al, 2020). It is promising to detect MRI-visible EPVS burden as a marker of cognitive decline in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, intracellular trafficking is emerging as a key regulator of diverse processes such as cell division, migration and secretion, thus confirming that MT dysfunction could be really detrimental for cells. Defects in the secretion pathways could be linked to many neurodegenerative disorders as suggested by recent evidences reporting changes in the serum levels of modulatory factors in patients affected by PD, MSA and AD . Notably, specific properties of MSCs cells include the secretion of a set of factors/molecules to the extracellular space, the so‐called secretome, whose crucial role in anti‐inflammatory response makes them a promising therapeutic tool .…”
Section: Discussionmentioning
confidence: 99%
“…Adefegha et al have reported that oral administration of Cd for 21 days may increases brain cholinesterase (both AChE and BChE) along with Na + /K + -ATPase) and monoamine oxidase activity [179]. Cholinesterase and Na + /K + -ATPase have been demonstrated for their involvement in the neurodegenerative diseases and also have considerable pharmacological relevance [180,181]. As stated above, brain inflammation further favors the initiation and progression of different brain diseases including cerebrovascular diseases [182].…”
Section: Cadmium (Cd)mentioning
confidence: 98%